A new method for the synthesis of diamantane by hydroisomerization of binor-S on treatment with sulfuric acid - Aminov, Rishat I.; Khusnutdinov, Ravil I. (Beilstein Journal of Organic Chemistry, 2020)
A new method was developed for the direct synthesis of the second representative of the homologous series of diamond-like hydrocarbons, diamantane, in 65% yield by hydroisomerization of the norbornadiene dimer, endo-endo-heptacyclo[8.4.0.02,12.03,8.04,6.05,9.011,13]tetradecane (binor-S) on treatment with concentrated sulfuric acid (98%). In the presence of H2SO4 of lower concentration (75–80%), the reaction stops after the hydrogenation step giving endo-endo-pentacyclo[7.3.1.12,5.18,10.03,7]tetradecane in 68% yield with excellent selectivity (100%).
Keywords: binor-S; diamantane; hydroisomerization; sulfuric acid; tetrahydrobinor-S

(untitled) - Murray, R. K.; Morgan, T. K.; Babiak, K. A. (J. Org. Chem., 1975)

(untitled) - Williams, V. Z., Jr; von Ragué Schleyer, P.; Gleicher, G. J.; Rodewald, L. B. (J. Am. Chem. Soc., 1966)

(untitled) - Mrowca, J. J.; Katz, T. J. (J. Am. Chem. Soc., 1966)

(untitled) - Gund, T. M.; Osawa, E.; Williams, V. Z.; Schleyer, P. v. R. (J. Org. Chem., 1974)

(untitled) - Aminov, R. I.; Khusnutdinov, R. I. (Russ. J. Org. Chem., 2017)

(untitled) - Gunchenko, P. A.; Novikovskii, A. A.; Byk, M. V.; Fokin, A. A. (Russ. J. Org. Chem., 2014)

(untitled) - Tureček, F.; Hanuš, V.; Sedmera, P.; Antropiusová, H.; Mach, K. (Collect. Czech. Chem. Commun., 1981)

(untitled) - Gund, T. M.; Thielecke, W.; Schleyer, P. v. R. (Org. Synth., 1973)

(untitled) - Dzhemilev, U. M.; Khusnutdinov, R. I.; Muslimov, Z. S.; Mazitov, M. F. (Pet. Chem., 1996)

(untitled) - Farooq, O.; Farnia, S. M. F.; Stephenson, M.; Olah, G. A. (J. Org. Chem., 1988)

(untitled) - Olah, G. A.; Wu, A.-h.; Farooq, O.; Prakash, G. K. S. (J. Org. Chem., 1989)

Russian Patent - Dzhemilev, U. M.; Khusnutdinov, R. I.; Kislitsina, K. S.; Kutepov, B. I.; Khazipova, A. N.; Travkina, O. S. (Method of producing diamantane (pentacyclo[7,3,1,14,12,02,7,06,11]tetradecane), 2012)

(untitled) - Khusnutdinov, R. I.; Muslimov, Z. S.; Dzhemilev, U. M.; Nefedov, O. M. (Russ. Chem. Bull., 1993)

(untitled) - Dzhemilev, U. M.; Khusnutdinov, R. I.; Muslimov, Z. S.; Tolstikov, G. A.; Nefedov, O. M. (Russ. Chem. Bull., 1991)

(untitled) - Karimi-Jaberi, Z.; Masoudi, B.; Rahmani, A.; Alborzi, K. (Polycyclic Aromat. Compd., 2020)

(untitled) - Schwertfeger, H.; Fokin, A. A.; Schreiner, P. R. (Angew. Chem., Int. Ed., 2008)

(untitled) - Hollowood, F. S.; McKervey, M. A.; Hamilton, R.; Rooney, J. J. (J. Org. Chem., 1980)

(untitled) - Kafka, Z.; Vodička, L.; Galík, V. (Collect. Czech. Chem. Commun., 1982)

(untitled) - Kafka, Z.; Vodicka, L. (Sb. Vys. Sk. Chem.-Technol. Praze, D: Technol. Paliv, 1985)

(untitled) - Kafka, Z. (Sb. Vys. Sk. Chem.-Technol. Praze, D: Technol. Paliv, 1991)

(untitled) - Kafka, Z.; Vodicka, L. (Sb. Vys. Sk. Chem.-Technol. Praze, D: Technol. Paliv, 1984)

(untitled) - Kafka, Z.; Nahunek, M. (Sb. Vys. Sk. Chem.-Technol. Praze, D: Technol. Paliv, 1986)

(untitled) - Kafka, Z.; Vodicka, L. (Sb. Vys. Sk. Chem.-Technol. Praze, D: Technol. Paliv, 1986)

(untitled) - Khusnutdinov, R. I.; Mukminov, R. R.; Aminov, R. I.; Khalilov, L. M.; Mesсheryakova, E. S.; Dzhemilev, U. M. (Tetrahedron Lett., 2015)

(untitled) - Aminov, R. I.; Akshieva, A. N.; Khusnutdinov, R. I. (Catal. Commun., 2019)